A Practical Application of IMC-PID Controller in Unmanned Vehicle - Qin Gang; Song Le; Hu Ling (Institute of Advanced Engineering and Science, 2013)
In allusion to unmanned vehicle steering control of the brushless DC motor control system, traditional PID controller parameter adjustment complex, weak ability to adapt to the environment and other issues, on the basis of the analysis of internal model control and classical PID control internal corresponding relationship, comprehensive its advantages, The design uses a brushless DC motor in the steering control system for unmanned vehicles based on the internal model PID controller ( IMC-PID) for speed. Based on the build object theoretical model, online simulation controller show that, for the design objects, based on the internal model PID controller whether the system step response or disturbance tracking control effect can reach the classic PID control requirements, also reduces the complexity and randomness of the design parameters. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2673